Does Land Use Planning shape Regional Economies? - Wouter Vermeulen; Jos van Ommeren (Tinbergen Institute, 2007)
Why has job growth over the past decades been weaker in the Dutch Randstad area than in surrounding regions? In a simultaneous equations analysis, we find that employment adjusts to the regional supply of labour. Net internal migration is predominantly determined by regional housing supply and not by employment growth. Growth of the regional housing stock responds only moderately to changes in the number of people and jobs. This lack of responsiveness to demand conditions is plausibly related to restrictions on residential development, implying that the regional distribution of economic activity in the Netherlands reflects land use planning decisions.
Keywords: J61; R12; R23; R31; R52; 330; housing supply; land use regulation; regional labour markets; regional development; Wohnungsmarkt; Angebot; Bodennutzung; Raumordnungsrecht; Regionaler Arbeitsmarkt; Regionale Entwicklung; Niederlande